Blood Injury and Injection Phobia: The Neglected One - Ab Latif Wani; Anjum Ara; Sajad Ahmad Bhat (Behavioural Neurology)
Blood injury and injection (BII) phobia is a unique phobia associated with a diphasic cardiovascular response. The aim of this survey was to report the prevalence of BII phobia, its heritability, and clinical characteristics among the males and females in the Indian subcontinent. An interview and a survey were conducted using a developed BII phobia 21-item questionnaire among 3261 participant males (n=1648) and females (n=1613). Cronbach’ alpha (α) of 0.972 of internal consistency was reported. The prevalence of BII phobia and associated fainting in females was slightly more than double in the males with a significant gender related effect. Similar avoidance behaviours involving hospital visits were reported for both males and females. The relative frequency of BII phobia among first and third degree relatives was found to be higher than among second degree relatives. Depression was found highly comorbid with BII phobia while a low rate of obsessive compulsion disorder (OCD) and social anxiety disorder (SAD) was reported. Morbidity associated with BII phobia may increase dramatically when other medical problems coincide with it.